Perancangan Game Puzzle sebagai Media Pembelajaran Aksara Sunda untuk Remaja - Rendra M. Ridwan; Alvanov Zpalanzani Mansoor; Ifa S. Mustikadara (Wimba : Jurnal Komunikasi Visual, 2013)
Sunda ethnic group have their own writing system, but because of various events in Indonesia, Sunda script is no longer used. After three centuries, West Java government and Sundanese scholars try to re-introduce the script. But teenagers, as one of potential target for Sundanese script socialization, have limited time learning this script in school, while there is also limited learning media for this script outside the school. To give teenagers a better interaction with Sundanese script, such as seeing, memorizing and writing, there is a need of instructional media for Sundanese script, outside the school. One of the media that can be used for learning purposes is game. Apart from the long history, game also known for the entertainment aspect and have a good impact for learning environment such as learning strategy findings, problem solving capability and intelectual, visual and motoric capability. With the possibilities to combine Sundanese script learning and game, this research designed to create entertaining learning media for students and broader audience, in attractive and fun alphabet learning process, outside the school environment. The Sundanese script game is designed using action research, compiling data from literature review about learning system, educational game, and Sundanese script. Data also contain expert interview about Sundanese script topic. After the required data is processed, learning system that is going to be used is rote learning, while the design frameworks used is intrinsic motivation for instructional environment. Research output is composed with rote learning sytem and puzzle genre, with the consideration of many implementation of language learning using this genre. There is wide range possibilty to using different learning method and different gameplay for the same purpose. This research able to be adapted for other Indonesia traditional writing system such as Batak, Java and other syllabic writing system.